BOSHLANG‘ICH SINF O‘QUVCHILARINING JISMONIY SIFATLARINI BAHOLASH TARTIBI - Erkaboyev, O.M. (SCIENCE and SOCIETY, 2025)
The article assessed the physical activity of primary school students and their level of physical fitness by quarters. The research results showed that students in grades 1-2 did not achieve initial results, and physical education programs were not sufficiently effective in school conditions. It was noted that the mandatory physical education classes held in schools are insufficient to eliminate the factor of hypodynamia (inaction), and it is also difficult to organize sports activities outside of school. According to the standards of physical activity established by the World Health Organization (WHO), the volume of physical education hours in our country is insufficient.